Conservative Treatment of Uterine Cervical Adenocarcinoma in Pregnancy. (17th December 2013) - Lima, Cid Almeida de; Barcelos, Ana Cristina Macêdo; Paschoini, Marina de Carvalho; Silva, João Henrique do Amaral e; Lima, Marcus Aurelho de; Murta, Eddie Fernando Candido; Nomelini, Rosekeila Simões
Abstract : Cancer of the cervix is the most common malignancy diagnosed during pregnancy, with an incidence of 1–10 cases per 10, 000 pregnancies. The desire of patients to maintain pregnancy and subsequent fertility is a difficult target to be achieved and should be widely studied, since it depends on the stage of disease, gestational age at diagnosis, and the woman's desire to maintain pregnancy. We describe in this report the case of a pregnant woman with invasive cervical adenocarcinoma in stage IB1 (FIGO) initially treated with neoadjuvant chemotherapy, followed by radical surgery and cesarean section in the same surgical procedure.